(untitled) (Global Journal of Medical Research, 2020)
Introduction and Objective: To determine the prevalence of emotional and behavioral problems among siblings of children with chronic neuromuscular illnesses by using validated parent completed assessment tool. Method: It is a cross-sectional study conducted in a tertiary care hospital from over a period of 34 months. Siblings of children with chronic neuromuscular illnesses were serially recruited while attending pediatric OPD and IPD. Parents were interviewed and requested to fill the Strength and Difficulty Questionnaire (SDQ) to assess and analyze emotional and behavioral problems among siblings. Results: Study included 171 siblings of children with chronic neuromuscular illnesses. Of 171 siblings, 124 (72.51%) had normal scores, 25 siblings (14.62%) were in borderline range and remaining 22 (12.87%) had abnormal values. The mean #xB1; SD of SDQ score was 12.41 #xB1; 3.6 with median score of 11. There was no significant difference between total SDQ scores of male vs female siblings (p value= 0.229) or between birth order of the sibling or GMFCS class of the affected child to emotional and behavioural problems. Subgroup analysis was not possible because of small sample size.